MAPPING TOURIST DESTINATION DESTINASIONS IN WEST PASAMAN REGENCY - Taufikri Taufikri (JURUSAN GEOGRAFI FIS UNP, 2021)
The development of the tourism sector is something that needs to be done by the local government because it gives a lot of benefits or benefits that can be taken, the tourism sector as part of economic activity is a potential mainstay and becomes a development priority for Indonesia's developing countries which have potential regions wide accompanied by a large tourist attraction. West Pasaman Regency has a variety of interesting natural attractions but because of limited time and distance traveled. This type of research used in this research is descriptive with a quantitative approach that is revealing problems that occur at the present time, based on calculations or numbers. Based on the results of the study that the distribution of attractions in West Pasaman Regency is very spread so that in every sub-district almost there are tourist objects that can be visited by local people and outside the region and transportation is one aspect that supports tourism activities, West Pasaman Regency in general has been crossed by the transportation network (Street). But some areas have road networks that are still in the form of dirt roads and some in the form of concrete and asphalt roads. Keywords: Traffic noise, Vegetation density, Distribution pattern